Combinando sistemas de informação geográfica e redes neurais GMDH para prever densidades demográficas - Brondino, Nair Cristina Margarido [UNESP]; Brondino, Odney Carlos (My University, 2012)
The aim of this work is to advance a new approach for estimating demographic density, through combining a Geographic Information System with GMDH Neural Networks. The model that is suggested parts the analyzed space into a rectangular grid formed by multiple cells measuring 0.01 km2 each. The forecasts are elaborated based on the demographic density in each cell and in its neighboring cells at a given time. Despite the limited availability of data during the modeling phase, the utilization of this method for studying a Brazilian medium-sized city presented promising results.

Artigo submetido em: 16/02/2011 Aceito para publicação em: 03/09/2012 Publicado em: 03/09/2012
Combining geographic information systems and gmdh neural networks to predict demographic density
Keywords: Geographic information system; Artificial neural networks; Demographic density; Sistema de informações geográficas; Redes neurais artificiais; Densidade demográfica